Peningkatan Aktivitas dan Hasil Belajar Matematika dengan Permainan Kartu Domino pada Siswa Kelas V SD - Doni Herwanto (Pedagogi: Jurnal Ilmu Pendidikan, 2019)
The research is inspired by the lack of activity of learners in the learning and low mathematics learning outcomes of the fifth grade students of Sekolah Dasar Negeri 13 Sungai Pinang. The purpose of this study was to describe the increase in activity and learning outcomes of students in class V SDN 13 Sungai Pinang on mathematic after using the game of dominoes. The hypothesis of action research is a game of dominoes can increase the activity and results of learning mathematics in Class V students of SDN 13 Sungai Pinang. This type of research, classroom action research. The subjects were fifth grade students of SDN 13 Sungai Pinang. The instrument used is the observation sheet activities of the learner, teacher activity observation sheet and test end of the cycle. Based on the research that has been carried out, it can be seen that the average value of the final exam cycle I was 70 with learning completeness percentage of 54.05%. From the analysis of activity observation sheet of students obtained an average percentage of observer II in the first cycle of 47.61%. After learning executed in the second cycle, the average obtained final replay value is 89.46 students with learning completeness percentage of 89.19%, while the average percentage of the activity of learners who obtained observer II is 84.80%. From the results obtained from the second cycle can be concluded that the learning of mathematics through a domino game method can increase the activity and learning outcomes of students in class V SD Negeri 13 Sungai Pinang.